PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN DI BMT NU SINGGAHAN TUBAN - Moch Zaenal Azis Muctharom; Moh. Agus Sifa' (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This article was conducted to determine the effect of providing rewards and punishment on employee performance at BMT NU Singgahan Tuban. The type of research used is in the form of field research using quantitative research methods in which primary data is obtained through interviews in the form of questionnaires (questionnaires to all BMT NU Singgahan Tuban employees with a sample size of 46 employees. The research consists of 3 variables which are where there are 2 variables The research was obtained through Hypothesis Testing consisting of a partial t-test. The results obtained were that the reward variable was significantly o,ooo and Punishment was significantly 0.040, which means the significant value was <0.05 and it could be said that variable Simultaneous F obtained a significant value of 0.000, which means <0.05 and it can be stated that variable